IFRS Meets the Realities of a Post-Communist Balkan State - David Alexander; Jonida Carungu; Stefania Vignini (Journal of Accounting and Management Information Systems (JAMIS), 2022)
Research Question - How will the Substance-over-Form (SoF) 'organism' survive, mutate and develop in a new and unfamiliar 'environment'? Motivation - Our study is motivated and inspired from a previous study published by Alexander et al. (2018) on "philosophy of language and accounting". Alexander et al. (2018) used the "Substance-over-Form" principle as a case study investigation of the practicability, or non-practicability, of harmonising changes in accounting regulation across seven countries (and six languages). The objective of this paper is to investigate on a very different context: Albania (an EU candidate country, an ex-communist "Balkan state", a different socially-constructed reality). Idea - This analysis shows the evolution of the SoF concept, by emphasizing the importance of the translation of official documents from English to Albanian and vice versa, comparing the content, the quality, and the level of translation in accounting. Data - We first analysed the main Albanian legislations on accounting from 1990 (opening year of the country to the free market economy) until 2021. Then, in order to assess the quality of translation from English to Albanian, we also critically examined the content and the level of translation of the 2018 IASB Conceptual Framework for Financial Reporting. Tools - The paper follows a deductive approach, as the results come from contextual data or clauses. A manual content analysis is implemented. Subsequently, a critical semantic analysis and an in-depth investigation on the level of translation of the accounting concepts, with an explicit focus on SoF treatment, is performed. Findings - The exposition, analysis and results are fully consistent with our theoretical framework, "social Darwinism". We add the Albanian case to previous studies, providing a contrasting scenario in that Albania has a significantly different history over recent decades. We illustrate a different socially-constructed reality from the seven countries of Alexander et al. (2018), and extend the overall understanding and the overall picture. The Albanian "organism" (accounting GAAP system) is consistent with its socially-constructed reality/environment. SoF seems to be distorted in its passage from Directive/IFRS originating sources, and this may well be fully consistent with local needs, realities, and cultures. Contribution - This research contributes to academic debate in three ways. First, it adds evidence to the literature on harmonisation processes, analysing the evolution of financial reporting regulation for a specific country and the application of a fundamental concept, such as SoF, comparing it to other national regulations. Second, this work contributes to further research, being a pioneer for the application of the "social Darwinism" to the analysis of a GAAP system. Finally, the paper contributes to the development of research on translation issues in accounting, by technically analysing the level of translation of the IASB Conceptual Framework for Financial Reporting and back-translating from national Laws.
Keywords: M41; 650; Financial Reporting; Post-Communism; Language in accounting; Comparability; Harmonisation (or dis-harmonisation); Social Darwinism